The claim of a diasporic intellectuality and epistemic diversity as a strategy (Práxis Educativa, 2022)
This article intends to understand the bases of the European colonial thought, seeing how the process of constitution of the University develops under the aegis of this paradigm. In this way, it was observed, from a literature review, that racial inclusion, promoted mainly by affirmative action policies, is not accompanied by structural reforms, from an epistemic, pedagogical and methodological point of view, that embrace the ontology of a diasporic student. However, the presence of minorities in Universities encourages denunciations about the consolidated Western universalism in the production of scientific knowledge. The University was also considered as a dislodging space for these existences and sought to make black insurgencies visible in the Academy, as well as to ventilate possibilities to encourage a truly emancipatory black intellectual activity.